The Impact of Social Media Engagement on Brand Love and Brand Loyalty among Generation Z in Indonesia - Evaf Maulina (The Eastasouth Management and Business, 2026)
This study examines the impact of social media engagement on brand love and brand loyalty among Generation Z consumers in Indonesia. A quantitative approach was employed, with data collected from 135 respondents through a structured survey using a Likert scale. The data were analyzed using Structural Equation Modeling (SEM-PLS 3.0). The results show that social media engagement significantly influences brand love, which in turn positively affects brand loyalty. Additionally, brand love was found to mediate the relationship between social media engagement and brand loyalty. These findings underscore the importance of emotional engagement in fostering long-term customer loyalty, particularly in the context of Generation Z’s high social media usage. Marketers aiming to engage this demographic should prioritize creating authentic and emotionally resonant content to foster brand love and loyalty.